Approaches to the creation of a systemic integrated theory of intellectual capital management - OZHIGANOV, E.N.; NAZYUTA, S. V.; CHURSIN, A.A.; OSTROVSKAYA, A.A. (The journal of contemporary issues in business and government, 2021)
Summary.:The present study aims to make its theoretical contribution to the rationale for the creation of an integrated system theory of human capital management and to clarify the interaction of knowledge generation factors in a dynamic innovation system. The systems theory of intellectual capital identifies the mechanisms that ensure the role of intellectual capital in the dynamic innovation capabilities of technology companies and industrial sectors.